2015
DOI: 10.1177/1938640015583511
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Obesity and Female Gender Among Patients With Concomitant Tibialis Posterior Tendonitis and Plantar Fasciitis

Abstract: The link between increased body weight and hindfoot complaints is largely based on correlation to single foot pathology. We retrospectively reviewed 6879 patients with tibialis posterior tendonitis (TPT), plantar fasciitis (PF), or both. Among patients with either TPT or PF, 1 in 11 (9%) had both. We then compared age, gender, and body mass index among these groups. Patients with both diagnoses were neither statistically older nor more obese than patients with single diagnoses. However, they were statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Moreover, to the best of our knowledge, BMI is the only variable associated with the extent of disability in patients with plantar fasciitis. 6,7,26 Few studies demonstrated that BMI values above normal were associated with plantar fasciitis. [27][28][29] In most studies, the patients were overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to the best of our knowledge, BMI is the only variable associated with the extent of disability in patients with plantar fasciitis. 6,7,26 Few studies demonstrated that BMI values above normal were associated with plantar fasciitis. [27][28][29] In most studies, the patients were overweight.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those recently reported by Reb and colleagues. 22 There are a few likely reasons for this finding. Women have increased arch laxity compared to men…”
Section: Limitationsmentioning
confidence: 99%
“…These findings are similar to those found by Reb and colleagues. 22 This trend may be attributed to differences in foot structure and function associated with aging, decreased physical activity level in the older middleaged and the elderly, and differences in access to health care resources across the lifespan. Changes in the foot associated with aging include decreased arch height, range of motion, plantar tactile sensation, and strength, and increased prevalence of foot deformity.…”
Section: Limitationsmentioning
confidence: 99%
“…In BMI overweight was specify in range of (25 to 29.9 kg/m 2 ) and obesity in range of (30 kg/m 2 or more than 30). 6,11 (Reb et al, 2015) reviewed the patients suffering from inflammation of the tendon of tibials posterior, plantar fasciitis. The ratio of tibials anterior tendinitis was 1 in 11 patients of plantar fasciitis.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion of collected data supported the connectivity between the foot pathologies and the obesity. 12 A study showed that rise in BMI, too long standing, and aggressive work could be cause of plantar fasciitis and other musculoskeletal related symptoms. The possibility feature like age and weight of the person, BMI or other type of medical histories compared to the history of work like too much standing or walking, standing at hard surface or doing heavy works is reasons for plantar heel pain.…”
Section: Introductionmentioning
confidence: 99%